Theologians as Interpreters—Not Prophets—in a Changing Climate - Clingerman, Forrest (Journal of the American Academy of Religion, 2015)
© The Author 2015. Published by Oxford University Press, on behalf of the American Academy of Religion. All rights reserved. For permissions, please e-mail: journals.permissions@oup.com - AS EXPRESSED BY TODD LEVASSEUR in the opening of this roundtable, the most recent IPCC report expressed a number of certainties, among them that climate change is occurring; that it will be disastrous for human well-being, not to mention a myriad of ecosystems and other species; and that it has been caused by industrial age activities. Furthermore, even though the impacts of climate change touch nearly every aspect of society, comprehensive mitigation and adaptation plans are not currently a significant part of U.S. public policy. For political and economic reasons, the United States does not seem capable of navigating the large number of potential tipping points and surprise effects that will define the speed and effects of climate change (see Lenton et al. 2008;...